Education and micronutrient deficiencies: an ecological study exploring interactions between women's schooling and children's micronutrient status. - Harding , Kassandra L.; Aguayo, Victor M.; Masters, William A.; Webb, Patrick. (Tufts University. Tisch Library., 2018)
Abstract: Formal education can be a nutrition-sensitive intervention that supports the scale-up and impact of nutrition-specific actions. Maternal education has long been linked to child survival, growth, and development while adult earnings and nutrition are tied to years in school as a child. However, less is known about the relationship between maternal education and the micronutrient status of children, women and the general population.; Keywords: Women's education, Micronutrients, Micronutrient deficiencies, Economic development.; Participating organizations: Friedman School of Nutrition Science and Policy, Tufts University, Yale School of Public Health, Yale University, BMC Public Health.; NIL publications.